استعمالات الارض الحضرية في مدينة الصلاحية - فائق رضا, عاتكة (Journal of College of Education, 2020)
Each city has multiple uses that share its territory even if that city is famous for a particular job, And spread in the al salahia city several basic uses of them such as (commercial, industrial, and residential) and non-basic such as (services, transportation and traffic), These uses form the internal structure of the city al-salahia, The functional and statistical approach was adopted in the study of land use, The city's origins were studied and the natural and human factors that affected its growth and the growth of urban uses were explained, The research also showed the areas and proportions for each use of the total city area and its percentage of the global area and clarify each use and preparation of its staff and locations of its spread, and reached several important conclusions and recommendations.